COMMON-EDGE SIGNED GRAPH OF A SIGNED GRAPH - Reddy, P. Siva Kota; Sampathkumar, E.; Subramanya, M. S. (Journal of the Indonesian Mathematical Society, 2010)
A Smarandachely k-signed graph (Smarandachely k-marked graph) is anordered pair....DOI :Â http://dx.doi.org/10.22342/jims.16.2.34.105-113